MYTHS IN ORGANIZATIONAL COMMUNICATION - Lazăr Ludmila (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2018)
Organizational culture is made up of several important elements, some visible, others less visible, underlying the communication processes that take place in organizations. The employees` behaviour is influenced by the core values of the institution, which are transmitted and enriched by myths, a kind of organizational “metaphors”. In the present study, we aim to identify the mythical archetypes, to elucidate the typology and characteristics of myths and their functions in the communication within organizations, to highlight the complexity of this valuable instrument of increasing the performance of the organization.